Fair Market Value of Used Capacity Assets: Forecasts for Repurposed Electric Vehicle Batteries - Bach, Amadeus; Onori, Simona; Reichelstein, Stefan; Zhuang, Jihan (The Accounting Review, 2026)
ABSTRACT In response to growing economic and environmental concerns, companies in a range of industries seek to repurpose products (assets) that retain functional capacity beyond their initial first life. This paper examines a generic valuation model for used capacity assets that can either be recycled immediately or repurposed for a second life application. We apply our model framework to lithium-ion batteries retired from electric vehicles, as these assets typically retain substantial energy storage capacity at the end of their first life. Our analysis focuses on two battery chemistries: lithium-iron-phosphate (LFP) and nickel-cobalt-X (NCX) based. We project their future fair market values in the United States and China. Our findings indicate that repurposing LFP batteries will be economically viable in both countries for the coming decade. In contrast, for most NCX batteries immediate recycling will soon be preferable due to their more valuable raw material content and shorter usable lives.